2023
DOI: 10.1371/journal.pone.0282475
|View full text |Cite
|
Sign up to set email alerts
|

Performing moderate to severe activity is safe and tolerable for healthy youth while wearing a cloth facemask

Abstract: Objective To investigate if a cloth facemask could affect physiological and perceptual responses to exercise at distinct exercise intensities in healthy young individuals. Methods Nine participants (sex, female/male: 6/3; age: 13±1 years; VO2peak: 44.5±5.5 mL/kg/min) underwent a progressive square-wave test at four intensities: (1) 80% of ventilatory anaerobic threshold (VAT), (2) VAT, and (3) 40% between VAT and V˙O2peak wearing a triple-layered cloth facemask or not. Participants then completed a final sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Additionally, the fact that wearing a face mask during exercise did not cause major physiological or perceptual impacts in healthy children reinforces our findings. 6 Also, face masks were fitted as tightly as possible, but inaccuracies in measurements owing to air escaping cannot be ruled out.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the fact that wearing a face mask during exercise did not cause major physiological or perceptual impacts in healthy children reinforces our findings. 6 Also, face masks were fitted as tightly as possible, but inaccuracies in measurements owing to air escaping cannot be ruled out.…”
mentioning
confidence: 99%
“…Despite important physiological differences between healthy children and adults during exercise, 5 we recently demonstrated that performing moderate to severe exercise while wearing a face mask is safe and tolerable for healthy youth, with no major impacts on cardiovascular, respiratory, and perceptual parameters during exercise. 6 This is further reinforced by a study that investigated face mask use in youth ice-hockey players, showing no impairment in performance, heart rate and oxygen saturation. 7 To our knowledge, however, there are no studies involving youth with obesity.…”
mentioning
confidence: 99%
See 3 more Smart Citations